Upaya Guru Dalam Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - fadlilah, Liya; Lutfiyah, Lujeng (ALMURTAJA: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this study was to analyze how teachers shape the social character of children at an early age in a school environment. This research uses qualitative descriptive techniques. Interviews, documentation, and observation are data collection techniques used in this study. The data analysis method used is interactive model triangulation, which combines data reduction, data presentation, and conclusion setting. The research took place at KB Islam Walisogo II Brondong, with instructors as research subjects. The results showed that teachers' Upayaes for developing children's personalities include responsibility, discipline, habits, student cooperation, mutual respect, and spontaneous activities. Using school culture to shape students' personalities. To instill character in their children, the teacher must have a strong and playful attitude. Teachers, in addition to being educators and instructors, can serve as role models for students. Keywords: early childhood; ece teacher; social devolepment